The impact of dividend taxation on dividends and investment : new evidence based on a natural experiment - Seppo Kari; Hanna Karikallio; Jukka Pirttilä (Center for Economic Studies and ifo Institute (CESifo), 2009)
There is a lack of clear evidence of the ways in which dividend taxation affects dividend distributions and investment since the evidence is based mainly on the behaviour of large listed companies. This paper utilises a large register-based panel data set, where the vast majority of firms are small and medium-sized enterprises, to examine the responses to the Finnish dividend tax increase of 2005. This reform creates a useful opportunity to measure enterprise behaviour, since it involves exogenous variation in the tax treatment of different types of firms. The results, based on differences-in-differences estimation and matching methods, indicate that dividends declined somewhat in closely held corporations that faced a tax increase, perhaps for timing reasons, while investments did not decline. These findings are more in line with the new rather than the old view of dividend taxation.
Keywords: H25; H32; 330; corporate income taxation; dividends; investment; tax reform; Körperschaftsteuer; Steuertarif; Steuerwirkung; Dividende; Investition; Klein- und Mittelunternehmen; Finnland